Perioperative complications of congenital diaphragmatic hernia repair - Barroso, Catarina (2018)
Although improvements have been made, the management of congenital diaphragmatic hernia (CDH) remains a major challenge for perinatologists and neonatal surgeons. Many aspects of the disease remain unknown and, being a rare entity, evidence-based data are hard to find. Surgical morbidity is considerable and affects long-term quality of life. Perioperative complications have been reviewed focusing on thoracoscopic repair. Intraoperative acidosis was more severe during thoracoscopy when compared with open surgery (OS), though it is possible that later neurodevelopment was not affected. Even so, strategies have been outlined to reduce acidosis, such as decreasing carbon dioxide (CO2) insufflation after reduction of the herniated viscera into the abdomen is complete. The risk of pleural complications decreased after introduction of gentle ventilation techniques and minimally invasive surgery (MIS); thus, the use of a prophylactic intraoperative thoracic tube is not routinely required. Recurrence rate was higher in large CDH and following MIS repair. Technical demands play an important role, therefore, in avoiding complications; every step of the OS technique must be strictly accomplished. In large defects, the use of prosthetic patch might reduce recurrence rate, even by MIS repair, once again only if technical demands are overcome with meticulous rules of suturing. Thoracoscopy significantly reduced the incidence of bowel obstruction and recovery time and improved cosmesis. The best approach of CDH is yet to be found, and it goes far beyond the management of perioperative complications. Meanwhile randomized controlled studies, namely on the outcome of thoracoscopic repair, are required to inform further practice.